(untitled) (Shaheed Smriti Journal, 2022)
This article explores the three fundamental domains of learning: cognitive, affective, and psychomotor. It highlights the importance of addressing these domains in teaching and learning to create a comprehensive and well-rounded educational experience. The cognitive domain focuses on knowledge acquisition, comprehension, application, analysis, synthesis, and assessment. The affective domain delves into emotions, attitudes, and values, influencing motivation and engagement. The psychomotor domain encompasses physical movements, coordination, and motor skills development. The article discusses each domain in detail, providing insights into enhancing cognitive abilities, promoting emotional well-being, and refining motor skills. It emphasizes the need for educators to integrate all three domains in instructional design to cater to diverse learning modalities and styles. The study utilizes a qualitative research design, drawing on secondary sources of data from related literature. By incorporating the cognitive, affective, and psychomotor domains, educators can create a dynamic and inclusive learning environment that fosters critical thinking, emotional resilience, and practical skills. The article concludes with implications for higher education institutions to adopt a comprehensive approach to education and design curricula that address these domains to meet the diverse needs of students.